Caregiver burden and coping strategies in schizophrenia: a hospital based study - Mishra, S.K.; Pandey, A.K.; Adhikari, B.R.; Nepal, S. (Journal of Psychiatrists' Association of Nepal, 2017)
Introduction: Schizophrenia is a severe mental illness which not only affects the patients but also causes significant distress to the caregivers, who use various strategies to minimize their distress. It is important to know about their suffering in order to include them in the treatment program. Objective: To assess the severity of burden and coping strategies among the caregivers Method: 36 admitted cases of patients and their caregivers were enrolled. Patients were assessed using PANSS while caregivers were assessed using BAS and COPE Inventory. Result: 47.2% caregivers reported suffering from severe burden. The most severely affected areas were physical and mental health, taking responsibility, caregiver's routine and patient's behavior. Caregivers used both problem oriented and emotion oriented strategy to minimize the distress. The choice of coping strategy and severity of burden was not influenced by the patient's symptoms. Conclusion: Caregivers of patients with schizophrenia suffered from significant burden and require additional care to help them alleviate their problems.